Customer Satisfaction Analysis of Sharia Services Quality at Surya Mart Ponorogo: (Case Study at Surya Mart Ponorogo Indonesia) - Maharani, Shinta; Rahman, Asmak Ab; Septian, Arif Dwi (European Journal of Islamic Finance, 2021)
This study aims to evaluate the level of satisfaction and service quality through CSI and IPA. The type of this study is quantitative approach under case study at Surya Mart Ponorogo Indonesia. The sample was 125 respondents. The variables of this study used sharia service quality and customer satisfaction composed of six dimensions: (1) compliance with Islamic law, (2) assurance, (3) reliability, (4) tangibility, (5) empathy, and (6) responsiveness, and each dimension has three statement attributes. Data were analyzed using Importance Performance Analysis (IPA), Cartesius Diagram, and Customer Satisfaction Index (CSI). The findings of this study are, firstly, the results of the IPA. The second finding is that the top priority attribute (indicated in Quadrant A of the Cartesian diagram) is sharia service quality. The third is a 75.2% value for customer satisfaction with the quality of sharia services at Surya Mart Supermarket Ponorogo, Indonesia, under CSI analysis, indicating that customers do feel satisfied enough.